2010
DOI: 10.1021/ie100896z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquids CnmimBr on Properties of Gemini Surfactant 12-3-12 Aqueous Solution

Abstract: The effect of ionic liquids C n mimBr (n ) 4, 6, 8) on the properties of cationic Gemini surfactant trimethylene-1,3-bis(dodecyl ammonium bromide) (Gemini 12-3-12) aqueous solution was investigated. The critical micelle concentration (cmc) of Gemini 12-3-12 solutions containing different amounts of ionic liquids were obtained by measurement of surface tension. The composition of mixed micelle and the interaction parameter between ionic liquids and Gemini 12-3-12 were calculated by Rubingh regular solution mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
1
44
2
Order By: Relevance
“…The results suggest that, with increasing IL concentration, the effective area per molecule at the interface increases, whereas the minimum area per molecule at the interface decreases to 0.6 wt%, thereafter followed by a reverse trend. Similar trends were observed when NaBr was added to the dimeric surfactant trimethylene-1,3-bis(dodecyl ammonium bromide (12-3-12) [82]. With the addition of NaBr, a continuous increase in C max and decrease in A min were observed, which is expected for an inorganic electrolyte [68,71].…”
Section: Surface Tension Measurementssupporting
confidence: 66%
See 1 more Smart Citation
“…The results suggest that, with increasing IL concentration, the effective area per molecule at the interface increases, whereas the minimum area per molecule at the interface decreases to 0.6 wt%, thereafter followed by a reverse trend. Similar trends were observed when NaBr was added to the dimeric surfactant trimethylene-1,3-bis(dodecyl ammonium bromide (12-3-12) [82]. With the addition of NaBr, a continuous increase in C max and decrease in A min were observed, which is expected for an inorganic electrolyte [68,71].…”
Section: Surface Tension Measurementssupporting
confidence: 66%
“…Javadian et al reported similar observation for the CTAB and SDS surfactants in the presence of ILs [66,67]. The addition of ILs changes the effective area of the surfactant molecule at the air-water interface in a parabolic manner [82]. The effective area is higher for [C 8 mim][Br] than for [C 6 mim][Br] due to the higher hydrophobicity.…”
Section: Additivementioning
confidence: 64%
“…Various physicochemical properties of surfactants have been reported to be much sensitive to molecular architecture and environmental conditions such as temperature, pressure, and additives [5][6][7][8][9][10]. Cationic Gemini surfactants were found to be less toxic and less persistent in the environment than the conventional quaternary ammonium surfactants [11,12]. Generally, Gemini surfactants that are symmetrical in the structure are called homogemini, whereas the asymmetrical dimeric surfactants are called heterogemini.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been dedicated to the development of gemini surfactants as they have a number of exclusive properties in contrast to conventional single-chain surfactants [8,9]. In general, Gemini surfactants have much lower CMC values, higher surface & Kallol K. Ghosh kallolkghosh@yahoo.com 1 activity, lower Krafft temperatures, interesting visco-elasticity properties and better lime-soap dissolving properties, and they are often better moistening agents [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%